Os significados de ser e formar-se professor: saberes mobilizados na formação em um curso de pedagogia - Souza, Antonio Carlos de (2010)
This research has had as its objectives to establish the meanings of being and to be formed a teacher and the knowledge mobilized for the formation in a Pedagogy Course, settled, a few years ago, in Sao Matheus district, eastern of São Paulo. We have proposed a student-teacher category trying to define the complex situation of those involved in teaching and those who are teachers and, due to a series of reasons, go to College and attend a Pedagogy Course, for teachers formation. We have tried not only to define the meanings that students-teachers give to their situation, but also to define the knowledge which is mobilized and tied to these established meanings. Considering these purposes, we have structured this thesis in four chapters: through the first one, we aimed at situating our object and understanding the complex relationships between: teacher formation and life in society; the curriculum; to be a teacher and the knowledge mobilized for training and teaching. In the second chapter, we uttered our methodological choices, procedures and instruments adopted. In the third one, we have described the plots and their subjects settings, teachers and students, and, as for the fourth chapter, we have discussed the data obtained, also presenting our interpretations. In our final remarks, we have thought back the trajectory taken, discussed our research and pointed to further possibilities of studies which our investigation has given rise to